Parental Awareness of Preventive Health Practices and Health-Related Quality of Life in Children with Cancer - Müberra Tanriverdi; Güleser Güney Yilmaz; İrem Nur Usluer; Hafize Reyhan Çalikuşu; Fatma Betül Çakir (Rehabilitation Oncology, 2026)
Background: This study aimed to examine parents’ awareness of health promotion and preventive care in childhood cancer and to investigate whether children’s HR-QoL (Health-Related Quality of Life) differs according to parental awareness items. Methods: This prospective cross-sectional study included 76 parents of children aged 0 to 18 years diagnosed with cancer and followed at a pediatric hematology/oncology clinic. Parents completed a Demographic Information Form, the Barratt Measure of Social Status, the Pediatric Quality of Life Inventory™ (PedsQL™) 3.0 Cancer Module, and a researcher-developed Health Promotion and Preventive Care Awareness Questionnaire. Differences in PedsQL total scores and socioeconomic status across awareness categories were analyzed using Mann–Whitney U and Kruskal–Wallis tests. Results: While most parents believed that cancer-related problems can be treated (92.1%) and prevented (76.3%), awareness of practical preventive care components was limited. Only 27.6% of parents reported knowing childhood cancer risk factors, 22.4% knew recommended physical activity levels, and 6.6% were aware of their child’s appropriate body mass index. Higher PedsQL total scores were observed among parents who believed cancer is preventable or treatable, knew recommended physical activity levels, and perceived their child as physically active ( P < 0.05). Socioeconomic status differed only for awareness of appropriate body mass index and physical activity recommendations. Discussion: These findings highlight the importance of behavior-oriented health promotion alongside disease-related education in pediatric oncology.